Lung-resident SARS-CoV-2 peptide-specific immune responses in perfused 3D human lung explant models - Goliwas, Kayla F.; Wood, Anthony M.; Simmons, Christopher S.; Khan, Rabisa; Khan, Saad A.; Wang, Yong; Ramachandran, Rekha; Berry, Joel L.; Athar, Mohammad; Mobley, James A.; Kim, Young-il; Thannickal, Victor J.; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMulti-specific and long-lasting T-cell immunity has been recognized to indicate long-term protection against pathogens, including the novel coronavirus, SARS-CoV-2, which is the causative agent of the COVID-19 pandemic. Functional significance of peripheral memory T cells in individuals recovered from COVID-19 (COVID-19+) is beginning to be appreciated; however, the role of lung tissue-resident memory (lung TRM) T cells in SARS-CoV-2 infection is still being investigated. This is, in part, due to the lack of preclinical tissue models available to follow the convalescence period.MethodsHere, we utilize a perfused three-dimensional (3D) human lung-tissue model and show pre-existing local T-cell immunity against SARS-CoV-2 proteins in lung tissues.ResultsWe report ex vivo maintenance of functional multi-specific IFN-γ-secreting lung TRM T cells in COVID-19+ and their induction in lung tissues of vaccinated COVID-19+ subjects. Importantly, we identify SARS-CoV-2 peptide-responding memory B cells and IgA+ plasma cells in ex vivo cultured lung tissues of COVID-19+. Furthermore, lung tissue IgA levels were increased in COVID-19+ and responded to peptide stimulation.DiscussionIn our study, we highlight the importance of utilization of human lung-tissue models to understand the local antiviral immune response in the lung to protect against SARS-CoV-2 infection.